HETEROGENEIDADE E CONFLITO NA INTERPRETAÇÃO DO QUILOMBO DOS PALMARES (Revista de História Regional, 2007)
In recent years historical archaeologists have become increasingly interestedin exploring how to use material culture to study conflict and how the interpretationof their sites is affected by modern perception. Grounded in a dialecticalepistemology, the experience of past peoples is considered part of an ongoingsocial confrontation between social actors. Archaeologists tend to considercultures as neatly bounded homogeneous entities. The holistic, monolithic natureof cultures has been put into question by several empirical and theoretical studies.In northeastern Brazil, a large maroon kingdom, Palmares, developed in the seventeenth century and people have often interpreted it in two ways. Someprefer to stress the African character of the polity, while others emphasize thediversity within the community. Archaeological research at Palmares producedevidence of a heterogeneous society, an interpretive model that does not followdominant epistemological schemes and prejudices.